Peningkatan Keterampilan Kader Sehat Dalam Pendampingan Ibu Nifas - Prastiwi, Dani; Vianti, Remilda Armika; Mastuti, Dewi Nugraheni Restu; Margarettha, Indi Laudya; Saputra, Dicky Aditia; Firdaus, M. Adnan; Agustin, Putri Stevany; Karimah, Luthfiyatul (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2025)
The postpartum period is a critical period for mothers and babies because a other does not only focus on herself,, but also on caring for her baby. Problems arise in postpartum service visits results in minimal information on ppostpartum vare. Community empowerment through improving the skills of cadres as companions for postpartum mothers is expected to solve problems in postpartum mothers. Community service activities will be carried out for 3 face to face meetings in Bandengan Village involving 6 active Posyandu with 21 people attending. Improving the knowledge and skills of cadres is carried out using a case study approach, group discussions, lectures and simulations. Assistance will be carried out by scheduling visits to postpartum mothers and conducting evaluations. There has been an increase in the knowledge and skills of cadres in assisting postpartum mothers. It is hoped that healthy cadres can become an extension of health workers in monitoring postpartum mothers and their babies, so that problems can be reduced.